Bibliometric Analysis: Research on Articulate Storylines in Mathematics Learning - Ilham Muhammad; Elmawati Elmawati; Christina Monika Samosir; Febrinna Marchy (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2023)
Articulate Storyline is part of the media authoring tools that can be used in making a product, especially for teaching tools that have been combined into one that contains images, videos, text, sound, drafts, and learning animations. This study aims to capture the landscape of previous research that is relevant to the Articulate Storyline in mathematics learning in the last decade, from 2013 to 2022 using bibliometric analysis. The data taken from the Google Scholar database was refined so that it became 111 publications. The publication trend related to Articulate Storyline in mathematics learning has increased every year, starting from 2019 to 2022, the most publications occurred in 2022 with 58 documents. Publications in 2020 have been cited in more than 180 citations. The focus of research related to Adobe Flash in learning mathematics is 1) critical thinking ability and motivation; 2) understanding mathematics, technology and elementary school; 3) development and junior high school; 4) mathematics and outcomes